PENGARUH LEADER MEMBER EXCHANGE DAN PEMBERDAYAAN TERHADAP KINERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi pada Pegawai Puskesmas di Dinas Kesehatan Kabupaten Batang) - Sukadar, Sukadar; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2015)
This study is aimed to find out the influence of Leader-Member Exchange and Empowerment to Performance with Organizational Citizenship Behavior as intervening variable. The population is all employees of District Health Office in Batang Regency, Central Java. The sample131employees was taken as respondents. The questionnaire was measured using Likert scale with seven options of answer. Validity and reliability test were conducted to test the instrument. While the test model used was determination coefficient and F test ( goodnes of Fit ) . Hypothesis test was done using regression analysis. Based on the result of the study, it can be summarized as: ( 1 ) Leader-Member Exchange does not influence Organizational Citizenship Behavior, ( 2 ) Empowerment positively significantly influences Organizational Citizenship Behavior, ( 3 ) LeaderMember Exchange does not influence Performance, ( 4 ) Empowerment positively significantly influences Performance, ( 5 ) Organizational Citizenship Behavior positively significantly influences Performance, ( 6 ) Organizational Citizenship Behavior does not mediate the influence of Leader-Member Exchange to Performance, ( 7 ) Organizational Citizenship Behavior mediates the influence of Empowerment to Performance.Keywords: leader-member exchange, empowerment, organizational citizenship behavior and performance.